Zinc nutrition to enhance rice productivity, zinc use efficiency, and grain biofortification under different production systems. Issue 1 (22nd November 2020) - Zulfiqar, Usman; Hussain, Saddam; Maqsood, Muhammad; Ishfaq, Muhammad; Ali, Nauman
Abstract: Zinc (Zn) deficiency is the most important abiotic factor limiting rice ( Oryza sativa L.) productivity and also a nutritional disorder with adverse impacts on human health worldwide. The present study investigated the comparative effect of four Zn application methods: Zn seed coating (2 g Zn kg −1 seed), Zn seed priming (0.25 M Zn solution), basal application (10 kg ha −1 ), and Zn foliar spray (0.5% Zn solution) in improving the productivity and biofortification of rice under puddled transplanted (PudTR) and direct‐seeded rice (DSR) system. A general control with no Zn application was included, whereas hydro‐priming and foliar water application were used as positive control treatments for Zn seed priming and Zn foliar spray, respectively. Regardless of application methods, Zn nutrition significantly improved the yield and related traits and grain Zn concentration in both production systems. Averaged across 2 yr, the increase in grain yield under different Zn application treatments was in the order of seed priming (23%) > foliar application (18%) > basal application (18%) > seed coating (13%), compared with the control. However, grain Zn concentration was the highest with seed priming in PudTR (33% over control) and with basal application in DSR (45% over control). The maximum net benefits were obtained through Zn seed priming in both production systems. In conclusion, Zn seed priming improved the yield and was the most cost‐effective method in PudTR and DSR system.